2009
DOI: 10.1111/j.1365-2133.2009.09309.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity in adult eczema

Abstract: This study indicates psychiatric comorbidity of adults with AE. Collaboration between dermatologists and mental health specialists may optimize medical care for a significant subgroup of patients with AE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 44 publications
7
56
1
3
Order By: Relevance
“…In patients with dermatological diseases in general, besides depressive and anxious symptomatology, other psychiatric disorders can occur, including schizophrenia, affective disorders, somatoform disorders, personality disorders, or behavioural disorders (Schmitt et al, 2009;Turčeková, 2012). We did not consider comorbidity of mental health or somatic diseases for inclusion of respondents in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with dermatological diseases in general, besides depressive and anxious symptomatology, other psychiatric disorders can occur, including schizophrenia, affective disorders, somatoform disorders, personality disorders, or behavioural disorders (Schmitt et al, 2009;Turčeková, 2012). We did not consider comorbidity of mental health or somatic diseases for inclusion of respondents in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies observed associations of eczema, hay fever or asthma with psychiatric conditions [38][39][40][41][42]. This is why mental health needs to be controlled for to see if there are independent associations of the respective condition with HRQoL impairments over and above that caused by mental health impairments.…”
Section: Introductionmentioning
confidence: 98%
“…Stress also enhances inflammatory cascades, endocrine imbalances and depletes the integument system's antimicrobial barrier that protects against cutaneous infection, reactivates skin disorders like eczema, stimulates acne and intensifies allergy symptoms [16,17]. These symptoms as well as the many other symptoms associated with stress are the same in CSAS.…”
Section: Understanding the Effects Of Stress Including Csasmentioning
confidence: 85%